The politics of Islam in Africa. Memories, revivals and Islamic populisms - (:unkn) unknown (My University, 2018)
In Africa, over the past thirty years or so, Muslim organizations have gained a foothold in the public arena, and have succeeded in creating a new political field that is defined less by institutions than by what people do politically. While state powers, converted to liberalism, are transferring political reason to the economic sphere, societies are simultaneously transferring this same reason to a religious sphere, where anyone can act politically without being perceived as doing so.The ongoing redefinition of public action through Islamic ethics is precisely what this book is about. From one re-enchantment to another, from the religious to the political, Islam as a space for the affirmation of an African identity enables us to re-read the continent's memories, awakenings and populisms. Between conservatism and post-modernity, faith and citizenship, ethics and public action, political Islam and the Islamization of politics, the politics of Islam in Africa proposes the establishment of democratic guidance for the state and society, under the aegis of the government of Allah.
Keywords: African Research